The limit state design of spun concrete columns using load combinations recommended by EN 1990 and ASCE/SEI 7–05 - Kudzys, Antanas; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2009)
The expediency of using precast spun concrete columns of annular cross‐sections reinforced by high‐strength steel bars is discussed. Test material properties, efficiency factors and resisting compressive stresses of plain and reinforced spun concretes are presented. Modelling a bearing capacity of eccentrically loaded members of annular cross‐sections is based on the concepts of compression with a bending moment and bending with a concentrical force. The comparison of test and modelling data of concentrically and eccentrically loaded members is analysed. The expediency to use in design practice the approaches of current methods of partial safety factors design (PSFD) legitimated in Europe and load and resistance factors design (LRFD) suggested in the USA and other countries is considered and illustrated by a numerical example. Santrauka Aptariamas didžiastiprio plieno strypais armuotų žiedinio skerspjūvio centrifuguotojo betono kolonų naudotinumas. Pateiktos armuotojo ir nearmuotojo centrifuguotojo betono medžiagų savybės, efektyvumo veiksniai ir laikomieji gniuždymo įtempiai. Ekscentriškai gniuždomų žiedinio skerspjūvio elementų laikomajai galiai modeliuoti taikomos lenkiamojo gniuždymo ir gniuždomojo lenkimo sampratos. Analizuojamas centriškai ir ekscentriškai apkrautų elementų eksperimentinių ir modeliavimo duomenų sugretinimas, nagrinėjamas Europos, JAV ir kitų šalių projektavimo praktikoje įteisintų ir paplitusių dalinių veiksnių ir apkrovų bei atsparių veiksnių metodų taikymo tikslingumas, kurį rodo skaitmeninis pavyzdys. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: centrifuguotasis betonas, didžiastipris plienas, gniuždymo bandymas, ekscentrinis apkrovimas, ribinių būvių metodas